Single cell–resolved cellular, transcriptional, and epigenetic changes in mouse T cell populations linked to age-associated immune decline - Jing He; Elena Burova; Chandrika Taduriyasas; Min Ni; Christina Adler; Yi Wei; Nicole Negron; Kun Xiong; Yu Bai; Tea Shavlakadze; Ella Ioffe; John C. Lin; et al. (Proceedings of the National Academy of Sciences, 2025)
Splenic T cells are pivotal to the immune system, yet their function deteriorates with age. To elucidate the specific aspects of T cell biology affected by aging, we conducted a comprehensive multi–time point single-cell RNA sequencing study, complemented by single-cell Assay for Transposase Accessible Chromatin (ATAC) sequencing and single-cell T cell repertoire (TCR) sequencing on splenic T cells from mice across 10 different age groups. This map of age-related changes in the distribution of T cell lineages and functional states reveals broad changes in T cell function and composition, including a prominent enrichment of Gzmk+ T cells in aged mice, encompassing both CD4+ and CD8+ T cell subsets. Notably, there is a marked decrease in TCR diversity across specific T cell populations in aged mice. We identified key pathways that may underlie the perturbation of T cell functions with aging, supporting cytotoxic T cell clonal expansion with age. This study provides insights into the aging process of splenic T cells and also highlights potential targets for therapeutic intervention to enhance immune function in the elderly. The dataset should serve as a resource for further research into age-related immune dysfunction and for identifying potential therapeutic strategies.